catena-Poly[[[triaquacadmium(II)]-μ-2,2′-[oxalylbis(azanediyl)]diacetato-κ(2) O,O′] dihydrate] - Zhou, Fangxia (International Union of Crystallography, 2009)
The structure of the polymeric title complex, {[Cd(C(6)H(6)N(2)O(6))(H(2)O)(3)]·2H(2)O}(n), consists of chains running parallel to [[Image: see text]01] in which the oxamidato ligand, deprotonated only at the carboxylate groups, acts as a bridging bis-monodentate ligand. The Cd atom and the O atom of a coordinated water molecule are located on a twofold axis. The coordination geometry around the Cd atom is distorted trigonal-pyramidal. In the crystal structure, neighbouring chains are linked into a three-dimensional network by interchain O—H⋯O and N—H⋯O hydrogen bonds.